Penguatan Modal Sosial Melalui Kenduri Blang Dalam Masyarakat Petani Di Gampong Krueng Batu Kecamatan Kluet Utara Kabupaten Aceh Selatan - Husna, Nurul; Azmi, Muhammad (JAROW: Journal of Ar-Raniry on Social Work, 2024)
This research entitled "Strengthening social capital through kenduri blang in farming communities" is motivated by the researcher's interest in strengthening social capital through kenduri blang in the farming community of Gampong Krueng Batu, North Kluet District, South Aceh Regency which has local wisdom about farming procedures among farming communities. The aim of this research is to find out how social capital is strengthened through kenduri blang in the farming community in Gampong Krueng Batu, North Kluet District, South Aceh Regency and what impact the kenduri blang has on strengthening social capital in the farming community. The research method used in this research is to use a research approach with a qualitative descriptive method. The data collection techniques used in this research to obtain data are observation, interviews and documentation. The results of this research show that there are 5 most important elements in strengthening social capital through kenduri blang for farming communities, including (1) Trust or confidence in farming communities, (2) Social solidarity or concern for farming communities, (3) Social values of farming communities, (4) Social norms of the farming community, and (5) Social networks of the farming community. There are several impacts obtained by the farming community in Krueng Batu gampong (1) Positive impacts, and (2) Negative impacts. A positive impact can be obtained if the community obeys and carries out the prohibitions and regulations that apply in the rice fields. Meanwhile, negative impacts are experienced if people do not comply with the prohibitions and regulations that apply in the rice fields.